Measures of prevention of operative field infections caused by vancomycin-resistant enterococci - Natalija Hadživuković; Biljana Mijović (Биомедицинска истраживања, 2019)
Introduction: Vancomycin-resistant enterococci (VRE) represent a major healthcare problem all around the world. The most effective methods for the control and prevention of these infections, as well as the methods controlling the growth of hospital-acquired VRE, have not been established yet. The aim of this systematic Reviews of the literature was to investigate the research papers concerned with various preventive measures against the operative field infections caused by VRE, as well as to examine the level of effectiveness of these measures in reducing the infection incidence rate. Methods: PubMed and EBSCO databases were used in order to find the research papers concerned with the measures for preventing the transmission of VRE. The process of searching for the above-mentioned databases was ended on 8 September 2018. Results: Using different combinations of the key words, the databases were thoroughly searched for, which led to the identification of 174 appropriate studies on the basis of the title and the abstract. After the detailed examination of the papers, based on the clearly defined criteria, 7 studies were included in the final analysis. The results showed that the VRE contamination was reduced to 70%, using the personal protective equipment such as aprons and gloves in all types of patient-centered interactions. Ecological cleaning, environmental and equipment disinfection as well as the rational use of antibiotics led to reduction in Clostridium difficile infection rates from 12% to 6.6 %, reduction in Staphylococcus aureus infection rates of 25%, while the rate of VRE bacteremia was also significantly lower. The number of patients whose isolation was required due to VRE infection was reduced. Conclusion: The current measures recommended by the Center for Disease Control and Prevention and used to prevent the spread of VRE are effective if the existing protocols are used adequately.
Keywords: vancomycin-resistant enterococci; operative field infections; preventive measures; active control